Inoperable bulky melanoma responds to neoadjuvant therapy with vemurafenib. (23rd October 2012) - Fadaki, Niloofar; Cardona-Huerta, Servando; Martineau, Lea; Thummala, Suresh; Cheng, Shih-Tsung; Bunker, Steve R; Garcia-Kennedy, Richard; Wang, Wei; Minor, David; Kashani-Sabet, Mohammed; Leong, Stanley P L
Abstract : A patient with a bulky inoperable stage IIIC melanoma involving the left axilla and neck from a primary of the left medial elbow received vemurafenib as neo-adjuvant treatment. Based on the molecular analysis, BRAF V600E mutation was present. After 4 months of vemurafinib treatment, the tumours shrank to less than 50% of original clinical size and allowed the surgeons to perform a left modified radical neck dissection and left radical axillary dissection. Pathological analysis of specimen revealed viable metastatic cells only in 1 of 40 nodes resected in the neck and axillary dissection, accounting for over 98% pathological response. Other lymph nodes had a mixture of foamy histiocytic inflammatory reaction fibrosis and islands of necrotic tissues. After recovery from surgery, vemurafenib was resumed and continued for 6 months. He remained disease free 6 months after surgery.